Customer satisfaction and purchasing intention in airline service quality: a case study of Malaysia Airlines - Hasim, Muhammad Asyraf; Shamsudin, Mohd Farid; Ishak, Mohd Fikri (SPC, 2018)
This study is an attempt to determine to what extent service quality impacts on passengers’ satisfaction and thus purchasing intentions of the flight between Kuala Lumpur and London by Malaysia Airlines. This study applied quantitative methodology to discover the relationship between service quality, customer satisfaction, and purchasing intentions among airline passengers. The study findings were based on a survey of 120 Malaysia Airlines passengers. Forty-eight British and seventy-two Malaysian passengers voluntarily took part in the survey of describing the level of passengers’ satisfaction and purchasing intention with the service provided by Malaysia Airlines between both nationalities. Five-point Likert scale was used to assess the respondents’ level of perception, satisfaction and purchasing intention. Results based on the data gathering and analysis show that, Malaysia Airlines’ passengers of both nationalities were at good level. This study shows that the service quality provided meet the expectations of passengers. Additionally, this study was only limited to the sample of Malaysia Airlines’ passengers who took part in the questionnaires. Further investigation in this area of research could deliver deeper information and findings to be useful to both academicians and practitioners.